2019
DOI: 10.1186/s13244-019-0714-x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in the diagnosis of ulnar nerve pathologies—a neoteric approach

Abstract: The ulnar nerve is a branch of the C8 and T1 nerve roots and arises from the medial cord of the brachial plexus. It supplies the intrinsic muscles of the hand and assists the median nerve in functioning of the flexors. Also known as the musician’s nerve, it is the second most common nerve involved in compressive neuropathy following the median nerve. Common sites of entrapment include cubital tunnel at the elbow, the ulnar groove in the humerus and the Guyon’s canal at the wrist. Patients present with altered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 51 publications
0
36
0
1
Order By: Relevance
“…reported that the diagnostic cut‐off values were more than 88% sensitive and specific for the diagnosis of cubital tunnel syndrome. Agarwal et al 29 . reported that ultrasound had an excellent diagnostic effect on ulnar nerve compression, and the abnormal morphological findings were consistent with what was seen during the operation, which suggests ultrasound diagnosis of cubital tunnel syndrome has important reference value for the staging of ulnar neuropathy and treatment methods choices.…”
Section: Discussionmentioning
confidence: 77%
“…reported that the diagnostic cut‐off values were more than 88% sensitive and specific for the diagnosis of cubital tunnel syndrome. Agarwal et al 29 . reported that ultrasound had an excellent diagnostic effect on ulnar nerve compression, and the abnormal morphological findings were consistent with what was seen during the operation, which suggests ultrasound diagnosis of cubital tunnel syndrome has important reference value for the staging of ulnar neuropathy and treatment methods choices.…”
Section: Discussionmentioning
confidence: 77%
“…The muscle-to-fat ratio of each muscle can further be graded according to the Goutallier classification [“grade 0 = no fat; grade 1 = few fatty streaks; grade 2 = <50% fat; grade 3 = 50 % fat, grade 4 = >50 % fat” ( 35 )]. Furthermore, lesions of soft-tissue structures, including blood vessels ( 67 ) and nerves ( 68 ), are clearly visible in MRI volumes. Additionally, intramuscular damage can be seen as muscle edema, which is ideally depicted using a T2-weigthed sequence sensitive for fluid [e.g., ( 31 )].…”
Section: Resultsmentioning
confidence: 99%
“…The MRI findings include ulnar nerve T2 hyperintensity approaching the adjacent ulnar collateral vessels, longitudinal extent of signal alteration, and enlargement or flattening of the ulnar nerve in the tunnel. It may be coupled with muscle denervation changes, manifesting as hyperintensity of the flexor carpi ulnaris and the ulnar portion of the flexor digitorum profundus on T2-weighted imaging [35] . While MR neurography and diffusion imaging are useful for ulnar neuropathy assessments, 3D anatomic MR imaging can outline the nerve along its long axis for depiction of primary and post-surgical re-entrapments and inflammatory neuropathies ( Fig.…”
Section: Anterior Compartmentmentioning
confidence: 99%